The increase in SARS-CoV-2 lineages during 2020–2022 in a state in the Brazilian Northeast is associated with a number of cases - Freitas, Moises Thiago de Souza; Sena, Ludmila Oliveira Carvalho; Fukutani, Kiyoshi Ferreira; Santos, Cliomar Alves dos; Neto, Francisco das Chagas Barros; Ribeiro, Julienne Sousa; dos Reis, Erica Santos; Balbino, Valdir de Queiroz; de Sá Paiva Leitão, Sérgio; de Aragão Batista, Marcus Vinicius; Lipscomb, Michael Wheeler; de Moura, Tatiana Rodrigues (Frontiers in Public Health, 2023)
SARS-CoV-2 has caused a high number of deaths in several countries. In Brazil, there were 37 million confirmed cases of COVID-19 and 700,000 deaths caused by the disease. The population size and heterogeneity of the Brazilian population should be considered in epidemiological surveillance due to the varied tropism of the virus. As such, municipalities and states must be factored in for their unique specificities, such as socioeconomic conditions and population distribution. Here, we investigate the spatiotemporal dispersion of emerging SARS-CoV-2 lineages and their dynamics in each microregion from Sergipe state, northeastern Brazil, in the first 3 years of the pandemic. We analyzed 586 genomes sequenced between March 2020 and November 2022 extracted from the GISAID database. Phylogenetic analyses were carried out for each data set to reconstruct evolutionary history. Finally, the existence of a correlation between the number of lineages and infection cases by SARS-CoV-2 was evaluated. Aracaju, the largest city in northeastern Brazil, had the highest number of samples sequenced. This represented 54.6% (320) of the genomes, and consequently, the largest number of lineages identified. Studies also analyzed the relationship between mean lineage distributions and mean monthly infections, daily cases, daily deaths, and hospitalizations of vaccinated and unvaccinated patients. For this, a correlation matrix was created. Results revealed that the increase in the average number of SARS-CoV-2 variants was related to the average number of SARS-CoV-2 cases in both unvaccinated and vaccinated individuals. Thus, our data indicate that it is necessary to maintain epidemiological surveillance, especially in capital cities, since they have a high rate of circulation of resident and non-resident inhabitants, which contributes to the dynamics of the virus.